Mutual Balance between Vasohibin-1 and Soluble VEGFR-1 in Endothelial Cells - Yasufumi Sato; Hiroki Miyashita; Akihide Ohkuchi; Hirotada Suzuki (MDPI AG, 2011)
Vasohibin-1 (VASH1) is a VEGF-inducible gene of endothelial cells (ECs) that acts as a negative feedback regulator of angiogenesis. To further characterize the function of VASH1, we transfected human VASH1 gene into the mouse EC line MS1, established stable VASH1 expressing clones, and determined gene alteration by cDNA microarray analysis. Among the various angiogenesis-related genes, vascular endothelial growth factor type 1 receptor (VEGFR-1) and its alternative spliced form, soluble VEGFR1 (sVEGFR-1), were found to be the most significantly down-regulated genes. Transient overexpression of VASH1 in human umbilical vein endothelial cells confirmed the down-regulation of VEGFR-1 and sVEGFR-1. sVEGFR-1 is a decoy receptor for VEGF and inhibits angiogenesis. Interestingly, when sVEGFR-1 was overexpressed in ECs, it inhibited the expression of VASH1 in turn. These results suggest that VASH1 and sVEGFR-1, two angiogenesis inhibitors, mutually balance their expressions in ECs.